Juridical Implications of Regional Regulations on the Management of Land Management Rights that have been Incorporated in Public Companies - Teuku Syahrul Ansari; Walman Gultom; Kharisma Gemilang; Aldiansyah Aldiansyah (Faculty of Law, Universitas Pekalongan, 2023)
Inbreng is a deposit of capital in forms other than money. BUMD Tbk. is a company whose capital is invested by the Regional Government Y in the form of Land Management Rights. This capital investment has been approved based on the Governor's Decree regarding Development Guidelines in the BUMD Tbk. Area, as well as giving BUMD Tbk. the right to provide recommendations on Land Management Rights. However, currently the Governor's Decree regarding Development Guidelines in the BUMD The Province of the Special Capital Region of Jakarta has the right to provide recommendations given by the Regional Government. As a result, BUMD Tbk. lost one of its income from providing recommendations. Apart from that, questions arise regarding the status of Land Management Rights which have become capital investments. Bearing in mind that BUMD Tbk. is a Public Company, BUMD This research will focus on Company Law and Capital Market Law. Especially according to the provisions of Financial Services Authority Regulation Number 42/POJK.04/2020 concerning Affiliate Transactions and Conflict of Interest Transactions and Financial Services Authority Regulation Number 17/POJK.04/2020 concerning Material Transactions and Changes in Business Activities